2019
DOI: 10.1177/2309499019870465
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of irreducible atlantoaxial dislocation using one-stage retropharyngeal release and posterior reduction

Abstract: Introduction: Irreducible atlantoaxial dislocation (IAAD) has been challenging for spine surgeons. Various methods have been used to treat IAAD, but no consensus has been reached. This study aimed to retrospectively analyze the efficacy of anterior submandibular retropharyngeal release and posterior reduction and fixation for IAAD. Methods: From March 2007 to May 2015, 13 patients diagnosed with IAAD underwent anterior submandibular retropharyngeal release and sequential posterior reduction and fixation. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…However, the transoral approach has a high risk of infection [15,21]. The anterior submandibular retropharyngeal approach is entirely extraoral and extramucosal, which reduces the rate of infection, while it may be difficult for patients with a big body habitus and short neck [20]. In our present study, the anterior release and posterior reduction and internal fixation were performed in 5 AAS patients without good reduction.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…However, the transoral approach has a high risk of infection [15,21]. The anterior submandibular retropharyngeal approach is entirely extraoral and extramucosal, which reduces the rate of infection, while it may be difficult for patients with a big body habitus and short neck [20]. In our present study, the anterior release and posterior reduction and internal fixation were performed in 5 AAS patients without good reduction.…”
Section: Discussionmentioning
confidence: 80%
“…For AAS without good reduction with the utility of skull traction under general anesthesia, sufficient release of the dislocated atlantoaxial joint is of key importance for successful treatment. In order to achieve good reduction, various methods had been used for IAAD patients, including transoral odontoidectomy and posterior fixation [15], transoral atlantoaxial reduction plate internal fixation [16,17], transoral atlantoaxial release and posterior internal fixation [18,19], and anterior submandibular retropharyngeal approach and posterior internal fixation [20]. All these procedures had advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Operative release and the pedicle screw technique have been able to achieve reduction in the dislocated atlantoaxial joint when traction reduction has been unsuccessful. [13][14][15] Therefore, considering operative release, the technique of three-dimensional CT and traumatic factors, we should distinguish atlantoaxial dislocations that can be reduced surgically from the others. In the present study, our TOI classification system is able to do that.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [17] demonstrated that the one-stage anterior transoral release and posterior internal xation were safe and reliable for treating IAAD. Ren et al [18] demonstrated the e cacy of anterior submandibular retropharyngeal release and posterior reduction and xation as the optimal treatment for patients with IAAD. In their study, all patients achieved satisfactory clinical outcomes without apparent complications including, pharyngeal or chest infection, deep vein thrombosis, or dyspnea postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, they determined that the majority of IAAD cases could become reducible after anterior release without odontoid resection. Thus, the clinical outcome of traditional treatments for IAAD was relatively satisfactory [18][19][20].…”
Section: Discussionmentioning
confidence: 99%